Answer:
k= -18
Step-by-step explanation:
5 = (k/6) + 8 so 5-8 = k/6
-3=k/6 then -3 multiplied by 6 = k which is -18 = k
-18/6= -3
-3+8=5
The formula is called the “midpoint formula”. It looks like this
m=(x1+x2)/2 , (y1+y2)/2 where m means midpoint. In your case it looks like this.
Answer:I think the answer is 5/12.
Step-by-step explanation:
Sorry if I am wrong. :) but it should be correct.
Answer:
b=i*
or -i*![\sqrt{\frac{59}{11} }](https://tex.z-dn.net/?f=%5Csqrt%7B%5Cfrac%7B59%7D%7B11%7D%20%7D)
Step-by-step explanation:
11b^2-9=-68
11b^2=-59
b^2=-59/11
b=i*
or -i*![\sqrt{\frac{59}{11} }](https://tex.z-dn.net/?f=%5Csqrt%7B%5Cfrac%7B59%7D%7B11%7D%20%7D)
"i" in this case is an imaginary number, equal to ![\sqrt{-1\\}](https://tex.z-dn.net/?f=%5Csqrt%7B-1%5C%5C%7D)
if you haven't learned about these yet, something is wrong with the question